Are the wild and laboratory insect populations different in semiochemical emission? The case of the medfly sex pheromone - Vaníčková, Lucie; do Nascimento, Ruth Rufino; Hoskovec, Michal; Ježková, Zuzana; Břízová, Radka; Tomčala, Aleš; Kalinová, Blanka (Journal of agricultural and food chemistry, 2012)
The medfly (Ceratitis capitata) is one of the major agricultural pests controlled through sterile insect technique (SIT) programs. We studied the chemical composition of the volatiles released by calling males from one laboratory and two wild C. capitata populations using two-dimensional gas chromatography with time-of-flight mass spectrometric detection (GC × GC/TOFMS) and gas chromatography with electroantennographic detection (GC-EAD). Multivariate data analyses revealed significant differences in the quantitative and qualitative composition of male chemical emanations between the three populations. The GC-EAD analyses of the male emanation of three C. capitata populations revealed 14 antenally active compounds. The volatiles isomenthone, β-pinene, ethyl octanoate, indole, geraniol, bornyl acetate, geranyl acetone, and (E)-caryophyllene are newly reported EAD active constituents of the male pheromone. GC-EAD analyses of the laboratory population indicated that the males and females of C. capitata possess comparable sensitivity to male-produced volatiles. Our results are relevant to the development of a pheromone-based monitoring system and also to the SIT control program.
Keywords: Animals; Chromatography, Gas; Female; Volatile Organic Compounds; ženské pohlaví; sexuální lákadla; laboratorní zvířata; hmotnostní spektrometrie; Ceratitis capitata; Animals, Laboratory; Male; plynová chromatografie s hmotnostně spektrometrickou detekcí; chromatografie plynová; Mass Spectrometry; Gas Chromatography-Mass Spectrometry; zvířata; mužské pohlaví; těkavé organické sloučeniny; Sex Attractants